Analisis Kualitas Pelayanan Perpajakan dalam Rangka Meningkatkan Kepatuhan Wajib Pajak (Studi Kasus Kpp Pratama Jakarta Senen 2018) - Maudy Zuraeva; Novianita Rulandari (Jurnal Pajak Vokasi (JUPASI), 2020)
This study aimed to determine the quality analysis of tax services at KPP Pratama Jakarta Senin in order to improve taxpayer compliance. The method used in this research was descriptive qualitative method. Data collection was carried out through interviews, observation and documentation. A total of eight informants were involved in this study.  Data analysis was performed using the Credibility and Transferability Test. The results of this study indicate that service indicators such as reliability, responsiveness, competence, access, courtesy, communication, credibility, security, understanding, and tangibles owned by tax employees of KPP Pratama Jakarta Senin are very good so that taxpayers are satisfied with the services they provide. However, there are still weaknesses in the courtesy indicator, in which some employees are not friendly, and in the tangibles indicator, in which the quality of human resources and the number of computer units is still lacking and the awareness and compliance of taxpayers is still low. These weaknesses have resulted in the failure to achieve the tax achievement target.